The relationship between audit experience and internal audit effectiveness in the public sector organizations - Badara, Mu'azu Saidu; Saidin, Siti Zabedah (Human Resource Management Academic Research Society, 2013)
Experience on organizational operations plays an important role in ensuring objective achievement of such organizations, likewise internal audit experience within an organizations contribute toward objective achievement of such organization.In line with this, the aim of this paper is to examine the relationship between audit experience and internal audit effectiveness in the public sector organizations.The paper is a literature review paper and the paper concluded that audit experience can influence the effectiveness of internal auditors in the public sector organizations. The paper needs to be validated empirically.